Double-beta-decay nuclear matrix elements in the QRPA framework - Suhonen, J. (2012)
We review the recent work done by the Jyväskylä-La Plata collaboration on the calculation of nuclear matrix elements for various modes of double-beta decays. Whenever helpful, we connect our recent work to the historical background in order to highlight the progress achieved in the field of double-beta decay. At the same time, we introduce some new concepts and ideas to treat e.g. possible backgrounds in Gamow-Teller strength functions generated in (p,n) and (n,p) reactions. © 2012 IOP Publishing Ltd.